Advancing reliability assessments of photovoltaic modules and materials using combined‐accelerated stress testing. (18th September 2020) - Owen‐Bellini, Michael; Hacke, Peter; Miller, David C.; Kempe, Michael D.; Spataru, Sergiu; Tanahashi, Tadanori; Mitterhofer, Stefan; Jankovec, Marko; Topič, Marko
Abstract: Previously undiscovered failure modes in photovoltaic (PV) modules continue to emerge in field installations despite passing protocols for design qualification and quality assurance. Failure to detect these modes prior to widespread use could be attributed to the limitations of present‐day standard accelerated stress tests (ASTs), which are primarily designed to identify known degradation or failure modes at the time of development by applying simultaneous or sequential stress factors (usually two at most). Here, we introduce an accelerated testing method known as the combined‐accelerated stress test (C‐AST), which simultaneously combines multiple stress factors of the natural environment. Simultaneous combination of multiple stress factors allows for improved identification of failure modes with better ability to detect modes not known a priori. A demonstration experiment was conducted that reproduced the field‐observed cracking of polyamide‐ (PA‐) and polyvinylidene fluoride (PVDF)–based backsheet films, a failure mode that was not detected by current design qualification and quality assurance testing requirements. In this work, a two‐phase testing protocol was implemented. The first cycle ("Tropical") is a predominantly high‐humidity and high‐temperature test designed to replicate harsh tropical climates. The second cycle ("Multi‐season") was designed to replicate drier and more temperate conditions found in continental or desert climates. Testing was conducted on 2 × 2‐cell crystalline‐silicon cell miniature modules constructed with both ultraviolet (UV)–transmitting and UV‐blocking encapsulants. Cracking failures were observed within a cumulative 120 days of the Tropical condition for one of the PA‐based backsheets and after 84 days of Tropical cycle followed by 42 days of the Multi‐season cycle for the PVDF‐based backsheet, which are both consistent with failures seen in fielded modules. In addition to backsheet cracking, degradation modes were observed including solder/interconnect fatigue, various light‐induced degradation modes, backsheet delamination, discoloration, corrosion, and cell cracking. The ability to simultaneously apply multiple stress factors may allow many of the test sequences within the standardized design qualification procedure to be performed using a single test setup. Abstract : A combined‐accelerated stress test was developed to better evaluate the reliability of photovoltaic modules and materials. A demonstration experiment was conducted which reproduced the cracking failures of some backsheets films, failure which could not be reproduced in standard stress tests. The test could also identify other degradation modes which are typically identified in the field.